2021
DOI: 10.2196/preprints.34385
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Concerns Around Opposition to the Green Pass in Italy: Social Listening Analysis by Using a Mixed Methods Approach (Preprint)

Abstract: BACKGROUND The recent introduction of COVID-19 certificates in several countries, including the introduction of a European Green Pass, has been met with protests and concerns by a fraction of the population. In Italy, the Green Pass has been used as a nudging measure to incentivize vaccinations, since unvaccinated people are not allowed to enter restaurants and bars, museums, or stadiums. OBJECTIVE … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…In line with previous research (21), we found that both respondents and GPT-3 were not able to distinguish whether a tweet was organic or synthetic (data on GPT-3's assessment are available in the study's repository) (15). It might be possible to develop specific training courses to improve humans' recognition of synthetic text, based on linguistic markers, grammatical structure, and syntax.…”
Section: "As Human As Humans": Synthetic Text Identification and Impe...supporting
confidence: 83%
See 4 more Smart Citations
“…In line with previous research (21), we found that both respondents and GPT-3 were not able to distinguish whether a tweet was organic or synthetic (data on GPT-3's assessment are available in the study's repository) (15). It might be possible to develop specific training courses to improve humans' recognition of synthetic text, based on linguistic markers, grammatical structure, and syntax.…”
Section: "As Human As Humans": Synthetic Text Identification and Impe...supporting
confidence: 83%
“…An effective and commonly used strategy involves impersonation. When GPT-3 declines to generate output that may breach content policies, users simply request it to impersonate a character, for which content policies apparently do not apply (22)(23)(24). With this approach, even more credible swathes of disinformation could be produced by first asking GPT-3 to generate fake profiles of people to impersonate and, in a second iteration, to generate tweets that these profiles could write.…”
Section: "As Human As Humans": Synthetic Text Identification and Impe...mentioning
confidence: 99%
See 3 more Smart Citations